The First Case of Yersinia pestis subsp. pestis Isolation in the Territory of the Altai Mountain Natural Plague Focus. Communication 2. Probable Ways and Mechanisms of Plague Agent Main Subspesies Importation into the Territory of the Focus - S. V. Balakhonov; V. M. Korzun; D. B. Verzhutsky; E. P. Mikhaylov; E. N. Rozhdestvensky; A. V. Denisov (Проблемы особо опасных инфекций, 2013)
Analysis of the epizootical situation in the North-West Mongolia and bordering regions of Russia has revealed the fact that plague agent of the main ssp., for the first time ever isolated in the Altai mountain natural plague focus in 2012, is imported from Serkh-Munkh-Khairkhan, which stands approximately 240 km away from it on the straight. It has been demonstrated that possibility of Yersinia pestis ssp. pestis transfer into the territory of Gorny Altai via slow natural migration of infected rodents, lagomorphs and their ectoparasites, as well as transmission by birds or terrestrial varmints in the mountainous environment over that large distance even within the period of several decades, is extremely negligible. The situation is conditioned by the presence of numerous physical-geographical barriers between the two regions involved and ecological peculiarities of the plague vectors and carriers. It is more likely that the agent of the main spp. has appeared in Gorny Altai due to the importation of infected fleas with isabelline wheatear ( Ocenanthe isabellina ) during a spring migration.